Utility of Rapid Diagnostic Test for the Diagnosis of Malaria in Children: A Cross-sectional Study - K Dhivya; M Manoj Kumar; J Ganesh (National Journal of Laboratory Medicine, 2023)
Introduction: Malaria is one of the primary causes of paediatric deaths. Rapid and accurate diagnosis, followed by effective treatment, is the main strategy for malaria control. Microscopy has been the gold standard test for diagnosing malaria for over a century. It offers good sensitivity, identifies various species, and measures parasitaemia levels. However, microscopy is time-consuming, labour-intensive, and requires technical expertise. Therefore, there is a need for an easily performed test that is more sensitive and reliable, especially in resource-limited settings. Rapid Diagnostic Tests (RDTs) are a viable alternative due to their simplicity, ease of use, accuracy, and reproducibility. Aim: To compare RDT with microscopy for diagnosis of malaria in children. Materials and Methods: This cross-sectional study was conducted in the Paediatric Ward of Government Stanley Medical College and Hospital, Chennai, Tamil Nadu, India, from September 2020 to February 2021. The study included children under 12 years of age with acute febrile illness, hepatosplenomegaly/splenomegaly, or anaemia and thrombocytopenia. Thick and thin blood smears, as well as RDT, were performed using venous samples. The collected data were analysed using the Statistical Package for the Social Sciences (SPSS) software version 23.0. To determine significance in categorical data, the Chi-square test/Fisher’s exact test was used. The efficacy was evaluated using the Receiver Operating Characteristic (ROC) curve, which provided sensitivity, specificity, positive predictive value, negative predictive value, and accuracy. Results: Among the 71 participants, 49 (69%) were males and 22 (31%) were females. Malaria presence, as determined by microscopy and RDT, was observed in 20 (28.2%) and 47 (66.2%) children, respectively, out of the total 71 enrolled in this study. The sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of RDT compared to microscopy were 100%, 48%, 44.7%, 100%, and 63.4%, respectively. The Area under the ROC (AUC) curve of RDT for diagnosing malaria was 0.740 (95% CI, 0.628 to 0.852; p-value=0.001). There was a statistically significant association between clinical response to antimalarials in microscopy-negative but RDT-positive subjects (p-value=0.0005). Conclusion: The present study demonstrates that RDT could be used as an alternative to microscopy in the diagnosis of malaria.